Vaccine Immunotherapy for Celiac Disease - Di Sabatino, Antonio; Lenti, Marco V.; Corazza, Gino R.; Gianfrani, Carmen (Frontiers in Medicine, 2018)
Autoimmune and allergic disorders are highly prevalent conditions in which an altered or abnormal immune response is mounted against self- or environmental antigens, respectively. Antigen-based immunotherapy is a therapeutic option aimed at restoring the specific immune tolerance towards pathogenic antigens while leaving the rest of the immune system unaffected. This strategy proved efficacy especially in allergic diseases, including asthma, allergic rhinitis, and food allergies, but still has shortcomings for the treatment of autoimmune diseases. However, there are no available therapies, currently, in clinical practice for restoring the physiological tolerance that is typically lost in autoimmune diseases. In celiac disease, which is a common immune-mediated enteropathy triggered by the ingestion of gluten in genetically susceptible individuals, antigen-based immunotherapy could be a feasible option thanks to our deep understanding of the pathogenic mechanisms underpinning this condition. In fact, the immunodominant gluten epitopes are well characterized and are recognized by pathogenic CD4+ T-cells that could be desensitized with immunotherapy. Moreover, the intestinal damage occurring in celiac disease (i.e., villous atrophy) is reversible upon gluten withdrawn. Only recently the results of a phase I trial of an intradermal, adjuvant-free, formulation of three specific gluten peptides (Nexvax2) showed a good safety profile, albeit its efficacy still needs to be demonstrated. More results are awaited, as they may radically change patients’ quality of life that is constrained by the lifelong gluten-free diet and by the potential onset of life-threatening complications.